Dietary Gluten as a Conditioning Factor of the Gut Microbiota in Celiac Disease. Issue 1 (9th August 2019) - Bascuñán, Karla A; Araya, Magdalena; Roncoroni, Leda; Doneda, Luisa; Elli, Luca
ABSTRACT: The gut microbiota plays a relevant role in determining an individual's health status, and the diet is a major factor in modulating the composition and function of gut microbiota. Gluten constitutes an essential dietary component in Western societies and is the environmental trigger of celiac disease. The presence/absence of gluten in the diet can change the diversity and proportions of the microbial communities constituting the gut microbiota. There is an intimate relation between gluten metabolism and celiac disease pathophysiology and gut microbiota; their interrelation defines intestinal health and homeostasis. Environmental factors modify the intestinal microbiota and, in turn, its changes modulate the mucosal and immune responses. Current evidence from studies of young and adult patients with celiac disease increasingly supports that dysbiosis (i.e., compositional and functional alterations of the gut microbiome) is present in celiac disease, but to what extent this is a cause or consequence of the disease and whether the different intestinal diseases (celiac disease, ulcerative colitis, Crohn disease) have specific change patterns is not yet clear. The use of bacterial-origin enzymes that help completion of gluten digestion is of interest because of the potential application as coadjuvant in the current treatment of celiac disease. In this narrative review, we address the current knowledge on the complex interaction between gluten digestion and metabolism, celiac disease, and the intestinal microbiota.